Uganda : Second Review Under the Policy Support Instrument and Request for Modification of Assessment Criteria. (IMF Staff Country Reports; Country Report ;, 2014)
This paper focuses on Uganda's Second Review Under the Policy Support Instrument (PSI) and Request for Modification of Assessment Criteria. Economic performance of Uganda has been broadly favorable. Progress has been made on structural reforms, but further steps are needed. Starting the construction of the two hydropower projects without further delay, approving and regulating the Public Financial Management Bill, and strengthening accounting controls are crucial steps in the reform effort. The expected amendments to the Bank of Uganda Act should support the inflation targeting regime. Based on the proposed policies, the IMF staff supports completion of the second PSI review.